PESERTA DIDIK DALAM PERSPEKTIF HADITS - Miharja, Sakrim (Universitas Islam Negeri Sunan Gunung Djati Bandung, 2016)
This article examines the students in the perspective of hadith. Hadith provide an idea of the ideal learner in order to achieve the expected educational goals of becoming scholars who basthotan fi ilmi and basthotan fi rizqi. Educators, learners and educational objectives have interrelated links between components of one component to another, so the educational process should be an integral and harmonious blend to produce an ideal education. Therefore, educational activities must deliver learners to achieve a life goal that has been outlined in Islamic teachings.